Three new species of the millipede genus Catharosoma Silvestri, 1897 from southern Brazil, with new records and a clarified identity of Catharosoma intermedium (Carl, 1902) (Diplopoda: Polydesmida: Paradoxosomatidae) - Rodrigues, Patrícia E. S.; Golovatch, Sergei I.; Ott, Ricardo; Rodrigues, Everton N. L. (Zootaxa, 2020)
Three new species of Catharosoma are described from southern Brazil: Catharosoma pedritense n. sp., Catharosoma promatense n. sp., and Catharosoma ibirapuitense n. sp.. New records of three other Catharosoma species, which considerably extend their distributions, are provided, including a redescription of the hitherto particularly poorly-known species Catharosoma intermedium (Carl, 1902).